ANALISIS KOMPONEN TATA KUALITAS LINGKUNGAN KAWASAN PECINAN KOTA MAGELANG - Arini, Siska; Suminar, Lintang (Jurnal Arsitektur ZONASI, 2023)
Pemuda Street which is located in the Chinatown area of Magelang City is located in a strategic location that connects Magelang City and Yogyakarta City. High density and activities make the street corridor a commercial corridor that is growing rapidly by time. Commercial activities which are also located in the Chinatown area also affect the environmental quality system that is formed. The research method used is descriptive method with a qualitative approach. The results showed that the distinctive character of the region as a trading area still looks strong with the existence of trading activities and other elements that support these activities. On the other hand, there is still a need for improvement in the aspect of facilities and sanctions for violating regulations.